Titanium alloy having dual state microstructure and method of making
Patent Information
- Application Number
- CN202410555011.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-05-07
AI Technical Summary
[0007]可见,目前的双态组织的钛合金,其热处理过程复杂,使得钛合金的成本变得很高,不利于低成本钛合金及其民用化
[0025] 1. The titanium alloy of the present invention with a dual-state structure has high hardness and tensile strength, and solid solution strengthening and precipitation phase strengthening are coordinated to improve the material properties.
Smart Images

Figure CN118326204B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to titanium alloys with a dual-state structure and their preparation methods, belonging to the field of titanium alloy technology. Background Technology
[0002] Titanium alloys possess many outstanding advantages, such as light weight, good corrosion resistance, and high specific strength, making them highly valuable in various material fields. However, titanium alloys also have some disadvantages, such as lower plasticity and toughness, and susceptibility to fatigue and stress corrosion damage.
[0003] To overcome these drawbacks, researchers have proposed a novel process—the titanium alloy dual-phase microstructure process. The titanium alloy dual-phase microstructure refers to the formation of two distinct grain structures within the material: fine-grained and coarse-grained, with a clear interface between them. This unique microstructure enhances the material's strength and toughness, while also increasing its fatigue resistance and corrosion resistance.
[0004] Currently, the dual-phase microstructure of titanium alloys is achieved through heat treatment. Specifically, the titanium alloy material is first heated to a high temperature and then rapidly cooled. During this process, the formation of fine and coarse grains depends on factors such as the material's chemical composition, heating rate, and cooling rate. At the high temperature, the microstructure of the titanium alloy changes, and the grains grow. Then, during rapid cooling, the grains in the material separate into two parts: larger coarse grains and smaller fine grains. This resulting dual-phase microstructure improves both the strength and toughness of the titanium alloy.
[0005] CN113862512A discloses a novel processing and manufacturing method for a high-strength and high-toughness high-temperature titanium alloy with a dual-state microstructure. The addition of a large amount of α-stabilizing elements (aluminum (Al), tin (Sn), zirconium (Zr)) strengthens the alloy, stabilizing the α phase and promoting the precipitation of lath α phase, which is beneficial for spheroidization of the lath α phase during hot working. Appropriate amounts of β-stabilizing elements (molybdenum (Mo), silicon (Si), tungsten (W)) supplement the strengthening while improving the durability and creep resistance of the titanium alloy. Boron (B) combines with titanium (Ti) to form the TiB phase. Since the TiB phase has extremely low solid solubility in the α and β phases of the titanium alloy, it is almost completely insoluble in the titanium alloy matrix and exists independently as short rods at the grain boundaries. During hot working, it can effectively inhibit the growth of β grains. A large amount of equiaxed non-Burgers α phase precipitates in the equiaxed or dual-state microstructure obtained through heat treatment, disrupting the orientation relationship between α and β phases and randomizing the orientation of the α phase crystals. The patented material contains a variety of elements, and requires heat treatment after smelting to obtain a bimodal structure.
[0006] CN114790533A discloses a heat treatment process for TC11 titanium alloy castings. Through a high-temperature solution treatment followed by gradient cooling, the TC11 alloy castings achieve a bimodal microstructure, with a room temperature tensile strength of 1070 MPa and an elongation exceeding 10%, while simultaneously reaching a tensile strength of 680 MPa at 500℃. This method still employs a special heat treatment process to obtain the bimodal microstructure.
[0007] It is evident that the current dual-state titanium alloys have complex heat treatment processes, which makes the cost of titanium alloys very high, hindering the development of low-cost titanium alloys and their civilian application. Summary of the Invention
[0008] To address the above deficiencies, the technical problem solved by this invention is to provide a titanium alloy with a dual-state structure that can be obtained without heat treatment, thereby reducing the cost of titanium alloys.
[0009] The present invention relates to a titanium alloy with a dual-state structure, which is composed of the following components in weight percentage: Nb: 0.1-5%, Co: 0.1-6%, Zr: 0.1-5%, Al: 0.1-5%, Fe: 0.1-2%, V: 0.1-2%, with the remainder being Ti and unavoidable impurities.
[0010] In one embodiment of the present invention, the titanium alloy comprises BCC body-centered cubic solid solution, HCP hexagonal solid solution, and FCC face-centered cubic solid solution; wherein the content of BCC body-centered cubic solid solution in the titanium alloy is 3-10%, the content of HCP hexagonal solid solution is 80-90%, and the content of FCC face-centered cubic solid solution is 4-6%.
[0011] In one embodiment of the present invention, the titanium alloy having a dual-state structure is composed of the following components by weight percentage: Nb: 2-3%, Co: 3-6%, Zr: 1-4%, Al: 2-4%, Fe: 1-3%, V: 1-2%, with the remainder being Ti and unavoidable impurities;
[0012] In one specific embodiment, the titanium alloy of the present invention having a dual-state structure is composed of the following components in weight percentage: Nb: 3%, Co: 3%, Zr: 4%, Al: 3%, Fe: 1%, V: 1%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 2%, Co: 4%, Zr: 2%, Al: 2%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 3%, Co: 5%, Zr: 1%, Al: 4%, Fe: 3%, V: 1%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 3%, Co: 6%, Zr: 3%, Al: 4%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities.
[0013] In one embodiment of the present invention, the titanium alloy has a tensile strength of 700–800 MPa, a yield strength of 600–700 MPa, and a hardness HRC of 18–25. In some specific embodiments, the titanium alloy has a tensile strength of 720–760 MPa, a yield strength of 640–685 MPa, and a hardness HRC of 18.6–21.8.
[0014] The present invention also provides a method for preparing the titanium alloy with a dual-state structure as described in the present invention.
[0015] The present invention provides a method for preparing a titanium alloy with a dual-state microstructure, comprising the following steps:
[0016] 1) Blank preparation: Take particles of seven metallic elements, Ti, Nb, Co, Zr, Al, Fe and V, ball mill them together, press them into blanks, put them into graphite crucibles coated with yttrium oxide, and then put them into an induction melting furnace;
[0017] 2) Melting: Vacuuming is performed to reduce the vacuum inside the melting furnace to below 10. -3 After Pa, argon gas is injected to bring the furnace pressure to 30-200 Pa, and the induction melting furnace is turned on to begin melting. The specific melting operation is as follows:
[0018] Heat to 800-1200℃ at a rate of 80-120℃ / min, hold for 4-6 min, then heat to 1600-2000℃ at a rate of 30-70℃ / min, hold for 15 min, then cool to 1000-1400℃ at a rate of 40-80℃ / min, and then cool with the furnace.
[0019] 3) Repeat the melting operation of step 2) at least once to obtain a titanium alloy with a dual-state structure.
[0020] In one embodiment of the present invention, in step 1), the purity of the metal element particles is 99.5-99.9%, and the average particle size is 2-6 mm.
[0021] In one embodiment of the present invention, in step 1), the mixture is stirred in a stainless steel ball mill jar for 10 to 30 minutes at a speed of 250 to 350 r / min; the billet is rod-shaped, and the pressing pressure is 30 to 50 MPa; preferably, the mixture is stirred in a stainless steel ball mill jar for 10 to 15 minutes at a speed of 300 r / min; and the pressing pressure is 40 MPa.
[0022] In one embodiment of the present invention, in step 2), the specific smelting operation is as follows: the temperature is raised to 1000°C at a rate of 100°C / min, held for 5 min, then raised to 1800°C at a rate of 50°C / min, held for 15 min, then cooled to 1200°C at a rate of 60°C / min, and then cooled with the furnace.
[0023] In one embodiment of the present invention, in step 3), the smelting step in step 2) is repeated 4 times.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The titanium alloy of the present invention with a dual-state structure has high hardness and tensile strength, and solid solution strengthening and precipitation phase strengthening are coordinated to improve the material properties.
[0026] 2. This invention achieves a dual-state microstructure by adjusting the composition, which can be directly obtained through casting, eliminating the need for cumbersome processes such as high-temperature deformation, recrystallization, and heat treatment.
[0027] 3. The method for preparing titanium alloys with dual-state structure of the present invention adopts vacuum induction melting, which does not require the development of new equipment, has low energy consumption, and can be completed within one hour, thus having good economic benefits. Attached Figure Description
[0028] Figure 1 The images show the XRD patterns of the titanium alloys prepared in Examples 1 to 4 of this invention.
[0029] Figure 2 The image shows the metallographic structure of the titanium alloy prepared in Example 1 of this invention, with the top left image magnified 100 times, the top right image magnified 200 times, and the bottom image magnified 500 times. Detailed Implementation
[0030] The present invention relates to a titanium alloy with a dual-state structure, which is composed of the following components in weight percentage: Nb: 0.1-5%, Co: 0.1-6%, Zr: 0.1-5%, Al: 0.1-5%, Fe: 0.1-2%, V: 0.1-2%, with the remainder being Ti and unavoidable impurities.
[0031] In one embodiment of the present invention, the titanium alloy comprises BCC body-centered cubic solid solution, HCP hexagonal solid solution, and FCC face-centered cubic solid solution; wherein the content of BCC body-centered cubic solid solution in the titanium alloy is 3-10%, the content of HCP hexagonal solid solution is 80-90%, and the content of FCC face-centered cubic solid solution is 4-6%.
[0032] In one embodiment of the present invention, the titanium alloy having a dual-state structure is composed of the following components by weight percentage: Nb: 2-3%, Co: 3-6%, Zr: 1-4%, Al: 2-4%, Fe: 1-3%, V: 1-2%, with the remainder being Ti and unavoidable impurities;
[0033] In one specific embodiment, the titanium alloy of the present invention having a dual-state structure is composed of the following components in weight percentage: Nb: 3%, Co: 3%, Zr: 4%, Al: 3%, Fe: 1%, V: 1%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 2%, Co: 4%, Zr: 2%, Al: 2%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 3%, Co: 5%, Zr: 1%, Al: 4%, Fe: 3%, V: 1%, with the remainder being Ti and unavoidable impurities; or composed of the following components in weight percentage: Nb: 3%, Co: 6%, Zr: 3%, Al: 4%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities.
[0034] In one embodiment of the present invention, the titanium alloy has a tensile strength of 700–800 MPa, a yield strength of 600–700 MPa, and a hardness HRC of 18–25. In some specific embodiments, the titanium alloy has a tensile strength of 720–760 MPa, a yield strength of 640–685 MPa, and a hardness HRC of 18.6–21.8.
[0035] The present invention also provides a method for preparing the titanium alloy with a dual-state structure as described in the present invention.
[0036] The present invention provides a method for preparing a titanium alloy with a dual-state microstructure, comprising the following steps:
[0037] 1) Blank preparation: Take particles of seven metallic elements, Ti, Nb, Co, Zr, Al, Fe and V, ball mill them together, press them into blanks, put them into graphite crucibles coated with yttrium oxide, and then put them into an induction melting furnace;
[0038] 2) Melting: Vacuuming is performed to reduce the vacuum inside the melting furnace to below 10. -3 After Pa, argon gas is injected to bring the furnace pressure to 30-200 Pa, and the induction melting furnace is turned on to begin melting. The specific melting operation is as follows:
[0039] Heat to 800-1200℃ at a rate of 80-120℃ / min, hold for 4-6 min, then heat to 1600-2000℃ at a rate of 30-70℃ / min, hold for 15 min, then cool to 1000-1400℃ at a rate of 40-80℃ / min, and then cool with the furnace.
[0040] 3) Repeat the melting operation of step 2) at least once to obtain a titanium alloy with a dual-state structure.
[0041] In one embodiment of the present invention, in step 1), the purity of the metal element particles is 99.5-99.9%, and the average particle size is 2-6 mm.
[0042] In one embodiment of the present invention, in step 1), the mixture is stirred in a stainless steel ball mill jar for 10 to 30 minutes at a speed of 250 to 350 r / min; the billet is rod-shaped, and the pressing pressure is 30 to 50 MPa; preferably, the mixture is stirred in a stainless steel ball mill jar for 10 to 15 minutes at a speed of 300 r / min; and the pressing pressure is 40 MPa.
[0043] In one embodiment of the present invention, in step 2), the specific smelting operation is as follows: the temperature is raised to 1000°C at a rate of 100°C / min, held for 5 min, then raised to 1800°C at a rate of 50°C / min, held for 15 min, then cooled to 1200°C at a rate of 60°C / min, and then cooled with the furnace.
[0044] In one embodiment of the present invention, in step 3), the smelting step in step 2) is repeated 4 times.
[0045] The specific embodiments of the present invention will be further described below with reference to examples, but the present invention is not limited to the scope of the embodiments described herein.
[0046] Example 1 (Case 1)
[0047] 1) Billet Preparation: Take raw material particles containing the constituent elements of titanium alloy, with a purity of 99.95% and an average particle size of 2-4 mm, consisting of seven metallic elements: Ti, Nb, Co, Zr, Al, Fe, and V. The mass percentages are: Ti: 85%, Nb: 3%, Co: 3%, Zr: 4%, Al: 3%, Fe: 1%, and V: 1%. Mix the materials in a ball mill for 10 minutes at 300 rpm; then press them into rods at a pressure of 40 MPa; place the pressed raw material into a graphite crucible coated with yttrium oxide, and then place it in an induction melting furnace for melting.
[0048] 2) Melting: First, use a mechanical pump to evacuate to below 5 Pa, then turn on the diffusion pump to evacuate to below 10 Pa. -3 After Pa, turn off the diffusion pump and inject argon gas to bring the furnace pressure to 100 Pa. Turn on the induction melting furnace to start melting, raise the temperature to 1000°C at a rate of 100°C / min, hold for 5 min, then raise the temperature to 1800°C at a rate of 50°C / min, hold for 15 min, then cool to 1200°C at a rate of 60°C / min, and then cool with the furnace.
[0049] 3) Repeat the melting step in step 2) four times to obtain a titanium alloy with a dual-state microstructure. Cut and characterize the alloy; its XRD pattern is shown below. Figure 1 Metallographic diagram (see diagram) Figure 2 The three images shown are metallographic images at 100x, 200x, and 500x magnification, respectively. They reveal a lamellar α-structure exhibiting a bundled, basket-weave-like pattern, with equiaxed primary α-phase present on its surface. The lamellar α-structure and the equiaxed primary α-phase together form a typical titanium alloy dual-state structure. This lamellar α-structure provides good plastic deformation capability, while the equiaxed primary α-phase has a pinning effect, preventing excessive elongation. Therefore, this structure possesses good toughness, plasticity, and high-temperature deformation capability.
[0050] Example 2 (Case 2)
[0051] 1) Billet Preparation: Take raw material particles containing the constituent elements of titanium alloy, with a purity of 99.95% and an average particle size of 2-4 mm, consisting of seven metallic elements: Ti, Nb, Co, Zr, Al, Fe, and V. The mass percentages are: Ti: 86%, Nb: 2%, Co: 4%, Zr: 2%, Al: 2%, Fe: 2%, and V: 2%. Mix in a ball mill jar for 10 minutes at 300 r / min; then press into rods using a press at a pressure of 40 MPa; place the pressed raw material into a graphite crucible coated with yttrium oxide, and then place it in an induction melting furnace for melting.
[0052] 2) Melting: First, use a mechanical pump to evacuate to below 5 Pa, then turn on the diffusion pump to evacuate to below 10 Pa. -3After Pa, turn off the diffusion pump and inject argon gas to bring the furnace pressure to 100 Pa. Turn on the induction melting furnace to start melting, raise the temperature to 1000°C at a rate of 100°C / min, hold for 5 min, then raise the temperature to 1800°C at a rate of 50°C / min, hold for 15 min, then cool to 1200°C at a rate of 60°C / min, and then cool with the furnace.
[0053] 3) Repeat the melting step in step 2) four times to obtain a two-phase titanium alloy. Its metallographic image is similar to... Figure 2 Similar. Cutting, testing, and characterization.
[0054] Example 3 (Case 3)
[0055] 1) Billet Preparation: Take raw material particles containing the constituent elements of titanium alloy, with a purity of 99.95% and an average particle size of 2-4 mm, consisting of seven metallic elements: Ti, Nb, Co, Zr, Al, Fe, and V. The mass percentages are: Ti: 82%, Nb: 3%, Co: 5%, Zr: 1%, Al: 4%, Fe: 3%, and V: 1%. Mix in a ball mill jar for 10 minutes at 300 r / min; then press into rods using a press at a pressure of 40 MPa; place the pressed raw material into a graphite crucible coated with yttrium oxide, and then place it in an induction melting furnace for melting.
[0056] 2) Melting: First, use a mechanical pump to evacuate to below 5 Pa, then turn on the diffusion pump to evacuate to below 10 Pa. -3 After Pa, turn off the diffusion pump and inject argon gas to bring the furnace pressure to 100 Pa. Turn on the induction melting furnace to start melting, raise the temperature to 1000°C at a rate of 100°C / min, hold for 5 min, then raise the temperature to 1800°C at a rate of 50°C / min, hold for 15 min, then cool to 1200°C at a rate of 60°C / min, and then cool with the furnace.
[0057] 3) Repeat the melting step in step 2) four times to obtain a two-phase titanium alloy. Its metallographic image is similar to... Figure 2 Similarly, cutting, testing, and characterization.
[0058] Example 4 (Case 4)
[0059] 1) Billet Preparation: Take raw material particles containing the constituent elements of titanium alloy, with a purity of 99.95% and an average particle size of 2-4 mm, consisting of seven metallic elements: Ti, Nb, Co, Zr, Al, Fe, and V. The mass percentages are: Ti: 80%, Nb: 3%, Co: 6%, Zr: 3%, Al: 4%, Fe: 2%, and V: 2%. Mix in a ball mill jar for 10 minutes at 300 r / min; then press into rods using a press at a pressure of 40 MPa; place the pressed raw material into a graphite crucible coated with yttrium oxide, and then place it in an induction melting furnace for melting.
[0060] 2) Melting: First, use a mechanical pump to evacuate to below 5 Pa, then turn on the diffusion pump to evacuate to below 10 Pa. -3 After Pa, turn off the diffusion pump and inject argon gas to bring the furnace pressure to 100 Pa. Turn on the induction melting furnace to start melting, raise the temperature to 1000°C at a rate of 100°C / min, hold for 5 min, then raise the temperature to 1800°C at a rate of 50°C / min, hold for 15 min, then cool to 1200°C at a rate of 60°C / min, and then cool with the furnace.
[0061] 3) Repeat the melting step in step 2) four times to obtain a two-phase titanium alloy. Its metallographic image is similar to... Figure 2 Similarly, cutting, testing, and characterization.
[0062] XRD patterns of Examples 1-4 Figure 1 Analysis revealed that all four embodiments consisted of three phases: BCC body-centered cubic solid solution, HCP hexagonal solid solution, and FCC face-centered cubic solid solution, but their contents varied. Quantitative analysis based on the intensity of each phase peak showed that the content of BCC body-centered cubic solid solution in the four embodiments was 3–10%, the content of HCP hexagonal solid solution was 80–90%, and the content of FCC face-centered cubic solid solution was 4–6%.
[0063] The mechanical properties of the titanium alloys prepared in Examples 1 to 4 were measured, and the results are shown in Table 1.
[0064] Table 1
[0065]
[0066]
[0067] It is evident that the titanium alloy of the present invention has a dual-state structure, high hardness, yield strength and tensile strength, and good mechanical properties.
Claims
1. A titanium alloy with a dual-state microstructure, characterized in that, Composed of the following components by weight percentage Composition: Nb: 2-3%, Co: 3-6%, Zr: 1-4%, Al: 2-4%, Fe: 1-3%, V: 1-2%, with the remainder being Ti and unavoidable impurities; the matrix of the titanium alloy is a lamellar α-structure, exhibiting a bundled basket weave pattern, with equiaxed primary α phases present on its surface; the titanium alloy includes BCC body-centered cubic solid solution, HCP hexagonal solid solution, and FCC face-centered cubic solid solution; wherein, the content of BCC body-centered cubic solid solution in the titanium alloy is 3-10%, the content of HCP hexagonal solid solution is 80-90%, and the content of FCC face-centered cubic solid solution is 4-6%; The preparation method of the titanium alloy includes the following steps: 1) Blank preparation: Take particles of seven metallic elements, Ti, Nb, Co, Zr, Al, Fe and V, ball mill them together, press them into blanks, put them into graphite crucibles coated with yttrium oxide, and then put them into an induction melting furnace; 2) Melting: After drawing a vacuum to make the vacuum inside the melting furnace lower than 10-3 Pa, argon gas is injected to make the pressure inside the furnace reach 30-200 Pa. The induction melting furnace is then turned on to start melting. The specific melting operation is as follows: heat up to 800-1200℃ at a rate of 80-120℃ / min, hold for 4-6 min, then heat up to 1600-2000℃ at a rate of 30-70℃ / min, hold for 15 min, then cool down to 1000-1400℃ at a rate of 40-80℃ / min, and then cool with the furnace. 3) Repeat the melting operation of step 2) at least once to obtain a titanium alloy with a dual-state structure.
2. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: Composed of the following components by weight percentage Composition: Nb: 3%, Co: 3%, Zr: 4%, Al: 3%, Fe: 1%, V: 1%, with the remainder being Ti and unavoidable impurities; Or composed of the following components by weight percentage Composition: Nb: 2%, Co: 4%, Zr: 2%, Al: 2%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities; Or composed of the following components by weight percentage Composition: Nb: 3%, Co: 5%, Zr: 1%, Al: 4%, Fe: 3%, V: 1%, with the remainder being Ti and unavoidable impurities; Or composed of the following components by weight percentage Composition: Nb: 3%, Co: 6%, Zr: 3%, Al: 4%, Fe: 2%, V: 2%, with the remainder being Ti and unavoidable impurities.
3. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: The titanium alloy has a tensile strength of 700-800 MPa, a yield strength of 600-700 MPa, and a hardness of HRC of 18-25.
4. The titanium alloy with a dual-state microstructure according to claim 3, characterized in that: The titanium alloy has a tensile strength of 720–760 MPa, a yield strength of 640–685 MPa, and a hardness of HRC of 18.6–21.
8.
5. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: In step 1), the purity of the metal element particles is 99.5-99.9%, and the average particle size is 2-6 mm.
6. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: In step 1), the mixture is mixed in a stainless steel ball mill jar for 10 to 30 minutes at a speed of 250 to 350 r / min; the billet is rod-shaped and the pressing pressure is 30 to 50 MPa.
7. The titanium alloy with a dual-state microstructure according to claim 6, characterized in that: Mix in a stainless steel ball mill jar for 10-15 minutes at a speed of 300 r / min; press at a pressure of 40 MPa.
8. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: In step 2), the specific smelting operation is as follows: heat up to 1000℃ at a rate of 100℃ / min, hold for 5min, then heat up to 1800℃ at a rate of 50℃ / min, hold for 15min, then cool down to 1200℃ at a rate of 60℃ / min, and then cool with the furnace.
9. The titanium alloy with a dual-state microstructure according to claim 1, characterized in that: In step 3), the smelting step in step 2) is repeated 4 times.
Citation Information
Patent Citations
Processing and manufacturing method of novel double-state-structure high-strength and high-toughness high-temperature titanium alloy
CN113862512A
Method for the manufacture of alpha-beta ti-al-v-mo-fe alloy sheets
CA2839303A1
Low-cost high-strength titanium alloy
CN116676509A